Composite film hot-pressing edge sealing process

Through the composite film hot pressed edge sealing process, the problems of structural instability and insufficient mechanical performance of composite films in edge sealing treatment are solved, and the production of high-quality packaging materials is realized, meeting the diversified market needs.

CN119659053APending Publication Date: 2025-03-21JIANGSU HUACHI MASCH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411737971.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing composite films have problems such as structural instability, insufficient mechanical performance and low production efficiency in edge sealing treatment, which is difficult to meet the market's diversified demand for high-quality packaging materials.

Method used

The composite film hot-pressed edge sealing process is adopted, and PP/GF composite film with high mechanical strength and stability is prepared through the steps of GF purification, etching treatment, drying, cutting, combing, hot-pressed edge sealing.

Benefits of technology

It significantly improves the structural stability and edge sealing quality of the composite film, reduces the scrap rate, shortens the production cycle, improves the production efficiency, and meets the market's diversified demand for high-quality packaging materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119659053A_ABST
    Figure CN119659053A_ABST
Patent Text Reader

Abstract

The invention provides a hot-pressing edge sealing process for a composite film, and belongs to the technical field of composite films, the influence of different GF addition amounts on the mechanical property of the composite film is systematically explored through tests, so that the optimal GF addition proportion is determined, and a solid foundation is laid for optimization of subsequent processes. Thirdly, further starting from the three key parameters of the hot-pressing temperature, the hot-pressing pressure and the hot-pressing time, aiming at the straight-strip-shaped edge sealing shape and the sawtooth-shaped edge sealing shape, the optimal edge sealing process conditions of the straight-strip-shaped edge sealing shape and the sawtooth-shaped edge sealing shape are deeply explored and determined; the structure stability of the composite film is remarkably improved, the edge sealing quality of the composite film is greatly improved, then the rejection rate is effectively reduced, the production period is greatly shortened, and the production efficiency is remarkably improved. Diversified requirements of the market on composite film products are met, and powerful technical support and guarantee are provided for continuous development of new markets and new fields for enterprises.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite films, in particular to a composite film hot pressing edge sealing process. Background Art

[0002] Composite membrane is a multilayer composite material that is made of two or more thin film materials combined into one by a specific composite process. Composite membrane is mainly composed of substrate, adhesive, processing aid, etc., and different materials are combined together by a specific composite process. Its structure usually includes a surface active layer (dense separation layer) with separation function and a porous layer that plays a supporting role.

[0003] Edge sealing is a crucial part of the composite film packaging process, which can effectively improve the sealing performance of the packaging. Through edge sealing, the edge of the composite film is tightly sealed to prevent external air, moisture, dust and other impurities from entering the interior of the package, thereby protecting the items in the package from contamination and damage. This is especially important for items that need to be stored or transported for a long time to ensure their quality and safety. After the composite film is edge sealed, its structural stability is significantly enhanced. Edge sealing makes the edge of the composite film more solid and less prone to breakage or tearing. This can not only extend the service life of the composite film, but also improve the reliability and safety of the packaging.

[0004] At present, composite films are mainly made of polyethylene (PE), polyester (PET), nylon (NY) and other materials, but they have disadvantages such as physical property limitations, problems in the production process and specific application limitations. PP / GF composite film, that is, a film made by compounding glass fiber (GF) with polypropylene (PP) matrix, can significantly improve its mechanical properties, such as tensile strength and fracture toughness, heat resistance, and barrier properties. In addition, PP / GF materials perform well in cost-effectiveness and can replace more expensive materials to a certain extent, helping to reduce production costs.

[0005] In view of the above problems, the present invention proposes a composite film hot pressing edge sealing process to enhance structural stability, improve the quality of composite film edge sealing, reduce scrap rate, shorten production cycle, improve production efficiency, meet the diversified market needs, and continuously open up new markets and new fields. Summary of the invention

[0006] The purpose of the present invention is to solve the above problems in the prior art and to propose a composite film hot pressing edge sealing process.

[0007] The object of the present invention can be achieved by the following technical scheme: A composite film hot pressing edge sealing process comprises the following steps:

[0008] S1 purification: Weigh a certain mass of GF and place it in a 500°C muffle furnace for heating and purification for 2.5 h to remove surface impurities.

[0009] Remove impurities such as oil and dust on the surface. If not removed, it may affect the interfacial bonding between GF and PP resin, thereby affecting the performance of the composite film. The purified GF has a purer surface, which is conducive to the processing and compounding in the subsequent steps.

[0010] S2 etching treatment: The purified GF is placed in a mixed solution of hydrochloric acid and sulfuric acid and etched at 70°C for 4 hours.

[0011] Etching treatment is used to increase the surface roughness of GF. The rough surface increases the contact area and mechanical bite force between GF and PP resin, thereby enhancing the interface bonding effect and helping to improve the overall performance and stability of the composite film.

[0012] S3 Drying: The GF after candle carving was washed with distilled water, placed in a vacuum oven, and dried at 100°C for 2h.

[0013] The purpose of drying is to remove moisture and residual solvent on the surface of GF to prevent them from having a negative impact on subsequent steps. At the same time, drying can also make the fiber structure of GF more stable, which is conducive to subsequent combing and compounding.

[0014] S4 cutting: Cut the acid-etched GF into short fibers with a length of about 35 mm.

[0015] The cut GF staple fibers have a uniform length, which is conducive to forming a uniformly distributed fiber web during the carding process.

[0016] S5 network preparation: a WL-GS-A roller carding machine is used to card the network.

[0017] The GF short fibers are combed into a web using a roller carding machine, and then stacked using a cross-lapping machine to obtain a multi-layer fiber web. This multi-layer fiber web has the characteristics of uniform fiber distribution in the longitudinal and transverse directions, greater surface density and thickness, which is beneficial to improving the strength and stability of the composite film.

[0018] S6 Preparation of PP film: PP pellets are hot-pressed by a vacuum laminator to prepare a PP film with a thickness of 0.2 mm.

[0019] S7 Preparation of composite film: placing GF meshes of different thicknesses between two layers of PP films for hot pressing and lamination to prepare PP / GF composite films.

[0020] S8 Cutting: Use a cutting machine to cut the composite film into required shapes and sizes.

[0021] The cut composite film has more precise size and shape, which is beneficial for subsequent processing and use.

[0022] S9 edge sealing: Use hot pressing to seal the edges.

[0023] The edge of the composite film is sealed by hot pressing to prevent fiber shedding and water penetration at the edge. The composite film after edge sealing has a more complete structure and better durability, which can meet a wider range of application requirements. At the same time, hot pressing edge sealing can also improve the aesthetics and overall quality of the composite film.

[0024] Preferably, in step S2, the mixed solution is specifically: 0.3 mol / L H 2 SO 4 Mix with 0.3 mol / L HCl in a 1:1 ratio.

[0025] Preferably, in step S5, when preparing the network, the feeding amount and the spacing of the GF are adjusted to obtain a uniform GF network, and the GF distribution of the single-layer GF network is longitudinal and transverse (along the machine running direction), and the gram weight is about 10g / m 2 .

[0026] Preferably, in step S7, the GF content is 0.2-0.8%, wherein the optimum addition amount is 0.2%.

[0027] Preferably, in step S9, the area of ​​the heat-pressed edge sealing is 3 to 5 cm.

[0028] Preferably, in step S9, two shapes of patterns are used for edge sealing, namely, straight edge sealing and serrated edge sealing.

[0029] Preferably, in step S9, the hot pressing edge sealing process parameters are: the hot pressing temperature is 180°C.

[0030] Preferably, in step S9, the hot pressing edge sealing process parameters are: the hot pressing pressure is 5 MPa.

[0031] Preferably, in step S9, the hot pressing edge sealing process parameters are: hot pressing time is 5 minutes.

[0032] Compared with the prior art, the composite film hot pressing edge sealing process has the following beneficial effects:

[0033] 1. The present invention provides a composite film hot pressing edge sealing process, which systematically tests different GF addition amounts to find the most significant addition ratio for improving the mechanical properties of the composite film. It not only enhances the mechanical strength of the film, but also provides scientific data support for subsequent process optimization, ensuring the quality and performance of the final product.

[0034] 2. The present invention provides a composite film hot-pressing edge sealing process. Based on the results of the previous GF addition exploration, the process optimization test can more effectively adjust the production parameters to fully utilize the strengthening effect of GF while reducing unnecessary material waste and production costs.

[0035] 3. The present invention provides a composite film hot pressing edge sealing process, which optimizes the hot pressing temperature through a single factor test to ensure good bonding between GF and the film substrate, while avoiding material degradation caused by excessively high temperature or weak bonding caused by excessively low temperature, which helps to improve the firmness of the edge sealing and the stability of the overall structure.

[0036] 4. The present invention provides a composite film hot pressing edge sealing process, which optimizes the hot pressing pressure through a single factor test to ensure that the material at the edge sealing part is tightly compacted and the formation of voids and bubbles is reduced, thereby improving the quality and aesthetics of the edge sealing and enhancing the overall strength and durability of the film.

[0037] 5. The present invention provides a composite film hot pressing edge sealing process, which optimizes the hot pressing time through a single factor test to ensure sufficient reaction and bonding between GF and the film substrate, while avoiding material aging due to too long hot pressing time or insufficient bonding due to too short time, thereby improving production efficiency and reducing scrap rate.

[0038] 6. The present invention provides a composite film hot-pressing edge sealing process, which explores different edge sealing shapes such as straight strips and serrated shapes to meet different application scenarios, improve product diversity and market competitiveness, and provide a basis for further process optimization.

[0039] In summary, the present invention provides a composite film hot pressing edge sealing process. First, through experiments, the influence of different GF addition amounts on the mechanical properties of the composite film is systematically explored, thereby determining the optimal GF addition ratio, which lays a solid foundation for the optimization of subsequent processes. Then, starting from the three key parameters of hot pressing temperature, hot pressing pressure and hot pressing time, the optimal edge sealing process conditions for straight strip and serrated edge sealing shapes are deeply explored and determined. It aims to significantly improve the structural stability of the composite film, greatly improve its edge sealing quality, and then effectively reduce the scrap rate, greatly shorten the production cycle, and significantly improve production efficiency. It not only meets the market's diversified demand for composite film products, but also provides strong technical support and guarantee for enterprises to continuously open up new markets and new fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 It is the DSC heating melting and cooling crystallization curve of the film in the specific embodiment 2.

[0041] Figure 2 This is a graph showing the tensile strength of the composite film at different temperatures in specific embodiment three.

[0042] Figure 3 This is a diagram of the fracture toughness of the composite film at different temperatures in specific embodiment 4.

[0043] Figure 4 This is a graph showing the tensile strength of the composite film under different pressures in the fifth specific embodiment.

[0044] Figure 5 This is a diagram of the fracture toughness of the composite film under different pressures in specific embodiment six.

[0045] Figure 6 This is a graph showing the tensile strength of the composite film at different times in specific embodiment seven. Figure 7 This is a diagram of the fracture toughness of the composite film at different times in specific embodiment eight. DETAILED DESCRIPTION

[0046] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments. Specific embodiment one:

[0048] A composite film hot pressing edge sealing process comprises the following steps:

[0049] S1 purification: Weigh a certain amount of GF and place it in a muffle furnace at 500℃ for 2.5h to remove surface impurities;

[0050] S2 etching treatment: In order to improve the surface roughness of GF and enhance the interfacial bonding with PP resin, the purified GF was placed in a mixed solution of hydrochloric acid and sulfuric acid and etched at 70°C for 4 hours;

[0051] S3 Drying: The GF after candle carving was washed with distilled water, placed in a vacuum oven, and dried at 100 °C for 2 h;

[0052] S4 cutting: cutting the acid-etched GF into short fibers with a length of about 35 mm;

[0053] S5 network preparation: WL-GS-A roller carding machine is used to card and form a web. According to the experimental needs, in order to obtain a fiber web with uniform fiber distribution in the longitudinal and transverse directions and a larger surface density and thickness, a cross-lapping machine, which is the downstream equipment of the carding machine, can be used to stack the webs to obtain a multi-layer fiber web;

[0054] S6 Preparation of PP film: PP pellets are hot-pressed by a vacuum laminator to prepare a PP film with a thickness of 0.2 mm;

[0055] S7: preparing composite film: placing GF nets of different thicknesses between two layers of PP films for hot pressing and laminating to prepare PP / GF composite film;

[0056] S8 Cutting: Use a cutting machine to cut the composite film into required shapes and sizes;

[0057] S9 edge sealing: Use hot pressing to seal the edges.

[0058] In step S2, the mixed solution is specifically: 0.3 mol / L H 2 SO 4 Mix with 0.3 mol / L HCl in a 1:1 ratio.

[0059] In step S5, when preparing the network, the feeding amount and the spacing of the GF are adjusted to obtain a uniform GF network. The GF distribution of the single-layer GF network is longitudinal and transverse (along the machine running direction), and the gram weight is about 10g / m 2 .

[0060] In step S7, the GF contents are 0%, 0.2%, 0.4%, 0.6% and 0.8% respectively.

[0061] In step S9, the area of ​​the heat-sealed edge is 3 to 5 cm.

[0062] In step S9, straight strips are used for edge sealing.

[0063] According to the above steps, various groups of composite films were prepared, namely PP, PP / GF-0.2%, PP / GF-0.4%, PP / GF-0.6%, and PP / GF-0.8%, and their mechanical properties were tested. The specific mechanical properties test method is as follows:

[0064] The mechanical properties test uses a universal electronic testing machine, and the test is based on the national standard GB / T1040-2006 "Determination of tensile properties of plastics". The sample preparation is to select samples with a cutting size of 10cm*1cm, 5 samples of each ratio (i.e. parallel samples), and use the average of the average times, i.e. the average of 5 times, to obtain the weighted average of the final analysis results as the experimental result. In the sample preparation process, the edges of the cut samples are required to be smooth and not rough, and do not affect the loading and unloading of the samples. The effective stretching length range is 50mm, the stretching speed set in the experiment is 50mm / min, and the upper and lower clamping distance is 50mm.

[0065] Results: The specific parameters of the mechanical properties of PP / GF composite films with five different GF addition amounts are shown in the following table.

[0066] Table 1 Mechanical properties of PP / GF composite film

[0067]

[0068] It can be seen from the table that compared with the PP group, the tensile strength of the PP / GF composite film with GF added is significantly enhanced, and when the GF addition is 0.2%, the tensile strength and fracture toughness of the PP / GF composite film are significantly improved. Compared with the pure PP film, the tensile strength of the PP / GF-0.2% film is increased by 36.63%, and the fracture toughness is increased by 40.89%. This is because GF is dispersed in the PP matrix in a network structure. When subjected to external force, the PP matrix can effectively transfer the load to the GF network, significantly improving the tensile strength and fracture toughness of the material. With the increase of GF content (0.6% and 0.8%), the fracture toughness and tensile strength of the PP / GF composite film tend to decrease. This is because the thickness of the GF network is large, and the wettability of the PP melt to the GF network is insufficient during hot pressing.

[0069] Specific example 2:

[0070] Specific Example 2 is a characterization of the thermodynamic properties of the PP / GF composite film mentioned in Specific Example 1. The DSC test can measure the thermal effects of the PP / GF composite film during heating or cooling, including key thermodynamic parameters such as specific heat capacity, phase transition temperature (such as melting temperature, crystallization temperature), and reaction heat. These parameters are crucial to understanding the thermal properties of the composite film and help evaluate its stability and reliability under different temperature environments. The content of Specific Example 2 is as follows:

[0071] 1)DSC test: weigh 6-8 mg of sample and 2 Under protection, DSC analysis was used to test the thermal behavior of the PP / GF composite film. The specific procedure was as follows: the temperature was raised from 40°C to 200°C at a heating rate of 10°C / min, and the heating curve of the PP / GF composite film was measured; then the temperature was lowered from 200°C to 30°C at a cooling rate of 10°C / min to obtain the non-isothermal crystallization curve of the PP / GF composite film. The crystallinity (X c ):

[0072] X c =△H / △H o ×100%

[0073] Where, △H: melting enthalpy of PP / GF composite film, J / g;

[0074] △H o : Melting enthalpy of PP when 100% crystallized, J / g.

[0075] 2) Results: The DSC heating melting and cooling crystallization curves of PP / GF composite film are as follows: Figure 1As shown in the figure, the DSC heating melting curve of the PP / GF-0.2% composite film has a peak value at about 170°C, and the cooling crystallization curve of the PP / GF-0.2% composite film has a peak value between 120 and 130°C.

[0076] Specific example three:

[0077] Specific Example 3 is a process optimization of a composite film hot-pressing edge sealing process mentioned in Specific Example 1. It is found from the test of different GF addition amounts that when the GF addition amount is 0.2%, the mechanical properties of the PP / GF composite film are optimal. Based on this addition amount, the optimal edge sealing temperature, edge sealing pressure and edge sealing time of the two edge sealing shapes are explored. The content of Specific Example 3 is as follows:

[0078] 1) Preparation of composite membrane

[0079] A certain amount of GF was weighed and placed in a muffle furnace at 500 °C for 2.5 h to remove surface impurities. The purified GF was placed in a mixed solution of hydrochloric acid and sulfuric acid (0.3 mol / L H 2 SO 4 and 0.3 mol / L HCI in a ratio of 1:1), and etched at 70°C for 4h; the GF after candle etching was washed with distilled water, placed in a vacuum oven, and dried at 100°C for 2h; the GF after the acid etching was cut into short fibers with a length of about 35mm; the WL-GS-A roller carding machine was used to card into a web. According to the experimental needs, in order to obtain a fiber web with uniform longitudinal and transverse distribution of fibers and a larger surface density and thickness, the cross-lapping machine of the carding machine can be used to stack the web to obtain a multi-layer fiber web. When preparing the network, the GF feed amount and spacing are adjusted to obtain a uniform GF web. The GF distribution of the single-layer GF web is longitudinal and transverse (along the machine running direction), and the gram weight is about 10g / m 2 ; PP pellets are hot-pressed by a vacuum laminator to prepare a PP film with a thickness of 0.2 mm; GF meshes of different thicknesses are placed between two layers of PP films for hot-pressing and compounding to prepare a PP / GF composite film with a GF content of 0.2%; a cutting machine is used to cut the composite film into required shapes and sizes; the edges are sealed by hot-pressing edge sealing, and the hot-pressing edge sealing area is 3 to 5 cm.

[0080] In step S9, in the hot pressing edge sealing process parameters, the hot pressing temperature is 100, 120, 140, 160, 180, 200°C.

[0081] In step S9, two shapes of patterns are used for edge banding, namely, straight edge banding and serrated edge banding.

[0082] 2) Composite membrane performance testing

[0083] The mechanical properties test uses a universal electronic testing machine, and the test is based on the national standard GB / T1040-2006 "Determination of tensile properties of plastics". The sample preparation is to select samples with a cutting size of 10cm*1cm, 5 samples of each ratio (i.e. parallel samples), and use the average of the average times, i.e. the average of 5 times, to obtain the weighted average of the final analysis results as the experimental result. In the sample preparation process, the edges of the cut samples are required to be smooth and not rough, and do not affect the loading and unloading of the samples. The effective stretching length range is 50mm, the stretching speed set in the experiment is 50mm / min, and the upper and lower clamping distance is 50mm.

[0084] 3) Results: The specific parameters of the tensile strength of PP / GF-0.2% composite films at different hot pressing temperatures are as follows Figure 2 As shown in the figure, it can be seen that the tensile strength of the PP / GF-0.2% composite film generally shows a trend of first increasing and then decreasing with the increase of the hot pressing temperature. When the hot pressing temperature is between 160 and 200°C, the tensile strength reaches a peak value, and the peak value may be around 180°C. The tensile strength of the straight edge banding is generally greater than that of the zigzag edge banding. This may be because the edge banding length at the short tooth position of the zigzag edge banding is reduced. After being stretched on both sides, the effective length becomes shorter and is easier to tear. Based on the above situation, the optimal hot pressing temperature of the PP / GF-0.2% composite film with straight or zigzag edge banding is 180°C. Specific embodiment four:

[0086] Specific Example 4 is a process optimization of a composite film hot-pressing edge sealing process mentioned in Specific Example 1. It is found from the test of different GF addition amounts that when the GF addition amount is 0.2%, the mechanical properties of the PP / GF composite film are optimal. Based on this addition amount, the optimal edge sealing temperature, edge sealing pressure and edge sealing time of the two edge sealing shapes are explored. The content of Specific Example 4 is as follows:

[0087] 1) Preparation of composite membrane

[0088] A certain amount of GF was weighed and placed in a muffle furnace at 500 °C for 2.5 h to remove surface impurities. The purified GF was placed in a mixed solution of hydrochloric acid and sulfuric acid (0.3 mol / L H 2 SO 4and 0.3 mol / L HCI in a ratio of 1:1), and etched at 70°C for 4h; the GF after candle etching was washed with distilled water, placed in a vacuum oven, and dried at 100°C for 2h; the GF after the acid etching was cut into short fibers with a length of about 35mm; the WL-GS-A roller carding machine was used to card into a web. According to the experimental needs, in order to obtain a fiber web with uniform longitudinal and transverse distribution of fibers and a larger surface density and thickness, the cross-lapping machine of the carding machine can be used to stack the web to obtain a multi-layer fiber web. When preparing the network, the GF feed amount and spacing are adjusted to obtain a uniform GF web. The GF distribution of the single-layer GF web is longitudinal and transverse (along the machine running direction), and the gram weight is about 10g / m 2 ; PP pellets are hot-pressed by a vacuum laminator to prepare a PP film with a thickness of 0.2 mm; GF meshes of different thicknesses are placed between two layers of PP films for hot-pressing and compounding to prepare a PP / GF composite film with a GF content of 0.2%; a cutting machine is used to cut the composite film into required shapes and sizes; the edges are sealed by hot-pressing edge sealing, and the hot-pressing edge sealing area is 3 to 5 cm.

[0089] In step S9, in the hot pressing edge sealing process parameters, the hot pressing temperature is 100, 120, 140, 160, 180, 200°C.

[0090] In step S9, two shapes of patterns are used for edge banding, namely, straight edge banding and serrated edge banding.

[0091] 2) Composite membrane performance testing

[0092] The mechanical properties test uses a universal electronic testing machine, and the test is based on the national standard GB / T1040-2006 "Determination of tensile properties of plastics". The sample preparation is to select samples with a cutting size of 10cm*1cm, 5 samples of each ratio (i.e. parallel samples), and use the average of the average times, i.e. the average of 5 times, to obtain the weighted average of the final analysis results as the experimental result. In the sample preparation process, the edges of the cut samples are required to be smooth and not rough, and do not affect the loading and unloading of the samples. The effective stretching length range is 50mm, the stretching speed set in the experiment is 50mm / min, and the upper and lower clamping distance is 50mm.

[0093] 3) Results: The specific parameters of the fracture toughness of PP / GF-0.2% composite films at different edge sealing temperatures are as follows Figure 3As shown in the figure, it can be seen that the fracture toughness of the PP / GF-0.2% composite film generally shows a trend of first increasing and then decreasing with the increase of hot pressing temperature, and the fracture toughness of the straight strip edge sealing and the zigzag edge sealing reaches a peak value when the hot pressing temperature is between 160 and 200°C, and the peak value may be around 180°C. Based on the above situation, the optimal hot pressing temperature of the PP / GF-0.2% composite film with straight strip or zigzag edge sealing is 180°C. Specific embodiment five:

[0095] Specific Example 5 is a process optimization of a composite film hot-pressing edge sealing process mentioned in Specific Example 3. It is found from the test of different GF addition amounts that when the GF addition amount is 0.2% and the edge sealing temperature is 180°C, the mechanical properties of the PP / GF composite film are optimal. Based on this addition amount and edge sealing temperature, the optimal edge sealing pressure and edge sealing time of the two edge sealing shapes are explored. The content of Specific Example 5 is as follows:

[0096] 1) Preparation of composite membrane

[0097] A certain amount of GF was weighed and placed in a muffle furnace at 500 °C for 2.5 h to remove surface impurities. The purified GF was placed in a mixed solution of hydrochloric acid and sulfuric acid (0.3 mol / L H 2 SO 4 and 0.3 mol / L HCI in a ratio of 1:1), and etched at 70°C for 4h; the GF after candle etching was washed with distilled water, placed in a vacuum oven, and dried at 100°C for 2h; the GF after the acid etching was cut into short fibers with a length of about 35mm; the WL-GS-A roller carding machine was used to card into a web. According to the experimental needs, in order to obtain a fiber web with uniform longitudinal and transverse distribution of fibers and a larger surface density and thickness, the cross-lapping machine of the carding machine can be used to stack the web to obtain a multi-layer fiber web. When preparing the network, the GF feed amount and spacing are adjusted to obtain a uniform GF web. The GF distribution of the single-layer GF web is longitudinal and transverse (along the machine running direction), and the gram weight is about 10g / m 2 ; PP pellets are hot-pressed by a vacuum laminator to prepare a PP film with a thickness of 0.2 mm; GF meshes of different thicknesses are placed between two layers of PP films for hot-pressing and compounding to prepare a PP / GF composite film with a GF content of 0.2%; a cutting machine is used to cut the composite film into required shapes and sizes; the edges are sealed by hot-pressing edge sealing, and the hot-pressing edge sealing area is 3 to 5 cm.

[0098] In step S9, in the hot pressing edge sealing process parameters, the hot pressing temperature is 180°C.

[0099] In step S9, two shapes of patterns are used for edge banding, namely, straight edge banding and serrated edge banding.

[0100] In step S9, in the hot pressing edge sealing process parameters, the hot pressing pressure is 3, 4, 5, 6, 7, 8 MPa.

[0101] 2) Composite membrane performance testing

[0102] The mechanical properties test uses a universal electronic testing machine, and the test is based on the national standard GB / T1040-2006 "Determination of tensile properties of plastics". The sample preparation is to select samples with a cutting size of 10cm*1cm, 5 samples of each ratio (i.e. parallel samples), and use the average of the average times, i.e. the average of 5 times, to obtain the weighted average of the final analysis results as the experimental result. In the sample preparation process, the edges of the cut samples are required to be smooth and not rough, and do not affect the loading and unloading of the samples. The effective stretching length range is 50mm, the stretching speed set in the experiment is 50mm / min, and the upper and lower clamping distance is 50mm.

[0103] 3) Results: The specific parameters of the tensile strength of PP / GF-0.2% composite films under different edge sealing pressures are as follows Figure 4 As shown in the figure. It can be seen that the tensile strength of the PP / GF-0.2% composite film with straight edge sealing shows a stable trend with the increase of hot pressing pressure, and shows the best tensile strength when the hot pressing pressure is 5MPa. The tensile strength of the PP / GF-0.2% composite film with zigzag edge sealing shows a trend of first increasing and then decreasing with the increase of hot pressing pressure, and shows the best tensile strength when the hot pressing pressure is 4-6MPa. In summary, the optimal hot pressing pressure for PP / GF-0.2% composite films with straight or zigzag edge sealing is 5MPa. Specific embodiment six:

[0105] Specific Example 6 is a process optimization of a composite film hot-pressing edge sealing process mentioned in Specific Example 4. It is found from the test of different GF addition amounts that when the GF addition amount is 0.2% and the edge sealing temperature is 180°C, the mechanical properties of the PP / GF composite film are optimal. Based on this addition amount and edge sealing temperature, the optimal edge sealing pressure and edge sealing time of the two edge sealing shapes are explored. The content of Specific Example 6 is as follows:

[0106] 1) Preparation of composite membrane

[0107] A certain amount of GF was weighed and placed in a muffle furnace at 500 °C for 2.5 h to remove surface impurities. The purified GF was placed in a mixed solution of hydrochloric acid and sulfuric acid (0.3 mol / L H 2 SO 4and 0.3 mol / L HCI in a ratio of 1:1), and etched at 70°C for 4h; the GF after candle etching was washed with distilled water, placed in a vacuum oven, and dried at 100°C for 2h; the GF after the acid etching was cut into short fibers with a length of about 35mm; the WL-GS-A roller carding machine was used to card into a web. According to the experimental needs, in order to obtain a fiber web with uniform longitudinal and transverse distribution of fibers and a larger surface density and thickness, the cross-lapping machine of the carding machine can be used to stack the web to obtain a multi-layer fiber web. When preparing the network, the GF feed amount and spacing are adjusted to obtain a uniform GF web. The GF distribution of the single-layer GF web is longitudinal and transverse (along the machine running direction), and the gram weight is about 10g / m 2 ; PP pellets are hot-pressed by a vacuum laminator to prepare a PP film with a thickness of 0.2 mm; GF meshes of different thicknesses are placed between two layers of PP films for hot-pressing and compounding to prepare a PP / GF composite film with a GF content of 0.2%; a cutting machine is used to cut the composite film into required shapes and sizes; the edges are sealed by hot-pressing edge sealing, and the hot-pressing edge sealing area is 3 to 5 cm.

[0108] In step S9, in the hot pressing edge sealing process parameters, the hot pressing temperature is 180°C.

[0109] In step S9, two shapes of patterns are used for edge banding, namely, straight edge banding and serrated edge banding.

[0110] In step S9, in the hot pressing edge sealing process parameters, the hot pressing pressure is 3, 4, 5, 6, 7, 8 MPa.

[0111] 2) Composite membrane performance testing

[0112] The mechanical properties test uses a universal electronic testing machine, and the test is based on the national standard GB / T1040-2006 "Determination of tensile properties of plastics". The sample preparation is to select samples with a cutting size of 10cm*1cm, 5 samples of each ratio (i.e. parallel samples), and use the average of the average times, i.e. the average of 5 times, to obtain the weighted average of the final analysis results as the experimental result. In the sample preparation process, the edges of the cut samples are required to be smooth and not rough, and do not affect the loading and unloading of the samples. The effective stretching length range is 50mm, the stretching speed set in the experiment is 50mm / min, and the upper and lower clamping distance is 50mm.

[0113] 3) Results: The specific parameters of the fracture toughness of PP / GF-0.2% composite films under different edge sealing pressures are as follows Figure 5 As shown. Figure 5It can be seen that the fracture toughness of the PP / GF-0.2% composite film with straight edge banding and zigzag edge banding shows a trend of first increasing and then fluctuating with the increase of hot pressing pressure, and has the best fracture toughness when the hot pressing pressure is 4-6MPa. In general, the optimal hot pressing pressure of the PP / GF-0.2% composite film with straight or zigzag edge banding is 5MPa. Specific embodiment seven:

[0115] Specific Example 7 is a process optimization of a composite film hot-pressing edge sealing process mentioned in Specific Example 5. It is found from the test of different GF addition amounts that when the GF addition amount is 0.2%, the edge sealing temperature is 180°C, and the edge sealing pressure is 5MPa, the mechanical properties of the PP / GF composite film are optimal. Based on this addition amount, edge sealing temperature and edge sealing pressure, the optimal edge sealing time of the two edge sealing shapes is explored. The content of Specific Example 7 is as follows:

[0116] 1) Preparation of composite membrane

[0117] A certain amount of GF was weighed and placed in a muffle furnace at 500 °C for 2.5 h to remove surface impurities. The purified GF was placed in a mixed solution of hydrochloric acid and sulfuric acid (0.3 mol / L H 2 SO 4 and 0.3 mol / L HCI in a ratio of 1:1), and etched at 70°C for 4h; the GF after candle etching was washed with distilled water, placed in a vacuum oven, and dried at 100°C for 2h; the GF after the acid etching was cut into short fibers with a length of about 35mm; the WL-GS-A roller carding machine was used to card into a web. According to the experimental needs, in order to obtain a fiber web with uniform longitudinal and transverse distribution of fibers and a larger surface density and thickness, the cross-lapping machine of the carding machine can be used to stack the web to obtain a multi-layer fiber web. When preparing the network, the GF feed amount and spacing are adjusted to obtain a uniform GF web. The GF distribution of the single-layer GF web is longitudinal and transverse (along the machine running direction), and the gram weight is about 10g / m 2 ; PP pellets are hot-pressed by a vacuum laminator to prepare a PP film with a thickness of 0.2 mm; GF meshes of different thicknesses are placed between two layers of PP films for hot-pressing and compounding to prepare a PP / GF composite film with a GF content of 0.2%; a cutting machine is used to cut the composite film into required shapes and sizes; the edges are sealed by hot-pressing edge sealing, and the hot-pressing edge sealing area is 3 to 5 cm.

[0118] In step S9, in the hot pressing edge sealing process parameters, the hot pressing temperature is 180°C.

[0119] In step S9, two shapes of patterns are used for edge banding, namely, straight edge banding and serrated edge banding.

[0120] In step S9, in the hot pressing edge sealing process parameters, the hot pressing pressure is 5 MPa.

[0121] In step S9, in the hot pressing edge sealing process parameters, the hot pressing time is 2, 3, 4, 5, 6, 7 minutes.

[0122] 2) Composite membrane performance testing

[0123] The mechanical properties test uses a universal electronic testing machine, and the test is based on the national standard GB / T1040-2006 "Determination of tensile properties of plastics". The sample preparation is to select samples with a cutting size of 10cm*1cm, 5 samples of each ratio (i.e. parallel samples), and use the average of the average times, i.e. the average of 5 times, to obtain the weighted average of the final analysis results as the experimental result. In the sample preparation process, the edges of the cut samples are required to be smooth and not rough, and do not affect the loading and unloading of the samples. The effective stretching length range is 50mm, the stretching speed set in the experiment is 50mm / min, and the upper and lower clamping distance is 50mm.

[0124] 3) Results: The specific parameters of the tensile strength of PP / GF-0.2% composite films at different edge sealing times are as follows Figure 6 As shown. Figure 6 It can be seen that the tensile strength of the PP / GF-0.2% composite film with straight strip and zigzag edge sealing shows a trend of first increasing and then decreasing with the increase of hot pressing time. It has the best tensile strength when the hot pressing time is within 4 to 6 minutes, and the peak value appears at about 5 minutes. In summary, the optimal hot pressing time for the PP / GF-0.2% composite film with straight strip or zigzag edge sealing is 5 minutes. Specific embodiment eight:

[0126] Specific Example 8 is a process optimization of a composite film hot-pressing edge sealing process mentioned in Specific Example 6. It is found from the test of different GF addition amounts that when the GF addition amount is 0.2%, the edge sealing temperature is 180°C, and the edge sealing pressure is 5MPa, the mechanical properties of the PP / GF composite film are optimal. Based on this addition amount, edge sealing temperature and edge sealing pressure, the optimal edge sealing time of the two edge sealing shapes is explored. The content of Specific Example 8 is as follows:

[0127] 1) Preparation of composite membrane

[0128] A certain amount of GF was weighed and placed in a muffle furnace at 500 °C for 2.5 h to remove surface impurities. The purified GF was placed in a mixed solution of hydrochloric acid and sulfuric acid (0.3 mol / L H 2 SO 4and 0.3 mol / L HCI in a ratio of 1:1), and etched at 70°C for 4h; the GF after candle etching was washed with distilled water, placed in a vacuum oven, and dried at 100°C for 2h; the GF after the acid etching was cut into short fibers with a length of about 35mm; the WL-GS-A roller carding machine was used to card into a web. According to the experimental needs, in order to obtain a fiber web with uniform longitudinal and transverse distribution of fibers and a larger surface density and thickness, the cross-lapping machine of the carding machine can be used to stack the web to obtain a multi-layer fiber web. When preparing the network, the GF feed amount and spacing are adjusted to obtain a uniform GF web. The GF distribution of the single-layer GF web is longitudinal and transverse (along the machine running direction), and the gram weight is about 10g / m 2 ; PP pellets are hot-pressed by a vacuum laminator to prepare a PP film with a thickness of 0.2 mm; GF meshes of different thicknesses are placed between two layers of PP films for hot-pressing and compounding to prepare a PP / GF composite film with a GF content of 0.2%; a cutting machine is used to cut the composite film into required shapes and sizes; the edges are sealed by hot-pressing edge sealing, and the hot-pressing edge sealing area is 3 to 5 cm.

[0129] In step S9, in the hot pressing edge sealing process parameters, the hot pressing temperature is 180°C.

[0130] In step S9, two shapes of patterns are used for edge banding, namely, straight edge banding and serrated edge banding.

[0131] In step S9, in the hot pressing edge sealing process parameters, the hot pressing pressure is 5 MPa.

[0132] In step S9, in the hot pressing edge sealing process parameters, the hot pressing time is 2, 3, 4, 5, 6, 7 minutes.

[0133] 2) Composite membrane performance testing

[0134] The mechanical properties test uses a universal electronic testing machine, and the test is based on the national standard GB / T1040-2006 "Determination of tensile properties of plastics". The sample preparation is to select samples with a cutting size of 10cm*1cm, 5 samples of each ratio (i.e. parallel samples), and use the average of the average times, i.e. the average of 5 times, to obtain the weighted average of the final analysis results as the experimental result. In the sample preparation process, the edges of the cut samples are required to be smooth and not rough, and do not affect the loading and unloading of the samples. The effective stretching length range is 50mm, the stretching speed set in the experiment is 50mm / min, and the upper and lower clamping distance is 50mm.

[0135] 3) Results: The specific parameters of the fracture toughness of the PP / GF-0.2% composite film at different edge sealing times are as follows Figure 7 As shown. Figure 7It can be seen that the fracture toughness of the PP / GF-0.2% composite film with straight strip and zigzag edge sealing shows a trend of first increasing and then decreasing with the increase of hot pressing time. It has the best fracture toughness when the hot pressing time is within 4 to 6 minutes, and the peak value appears at about 5 minutes. In summary, the optimal hot pressing time for the PP / GF-0.2% composite film with straight strip or zigzag edge sealing is 5 minutes.

[0136] 4) Conclusion: From the above results, it can be seen that for PP / GF-0.2% composite film, when the edge sealing shape is straight strip or zigzag, the optimal hot pressing edge sealing process uses a hot pressing temperature of 180°C, a hot pressing pressure of 5 MPa, and a hot pressing time of 5 min to obtain a composite film with optimal tensile strength and fracture toughness.

[0137] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.

Claims

1. A composite film hot pressing edge sealing process, characterized in that: The steps include: S1 purification: Weigh a certain amount of GF and place it in a muffle furnace at 500℃ for 2.5h to remove surface impurities; S2 etching treatment: the purified GF was placed in a mixed solution of hydrochloric acid and sulfuric acid and etched at 70°C for 4 hours; S3 Drying: The GF after candle carving was washed with distilled water, placed in a vacuum oven, and dried at 100 °C for 2 h; S4 cutting: cutting the acid-etched GF into short fibers with a length of about 35 mm; S5 network preparation: using a WL-GS-A roller carding machine to card into a network; S6 Preparation of PP film: PP pellets are hot-pressed by a vacuum laminator to prepare a PP film with a thickness of 0.2 mm; S7: preparing composite film: placing GF nets of different thicknesses between two layers of PP films for hot pressing and laminating to prepare PP / GF composite film; S8 Cutting: Use a cutting machine to cut the composite film into required shapes and sizes; S9 edge sealing: Use hot pressing to seal the edges.

2. The composite film hot pressing edge sealing process according to claim 1, characterized in that: In step S2, the mixed solution is specifically: 0.3 mol / L H2SO4 and 0.3 mol / L HCl are mixed in a ratio of 1:

1.

3. The composite film hot pressing edge sealing process according to claim 1, characterized in that: In step S5, when preparing the network, the feeding amount and the spacing of the GF are adjusted to obtain a uniform GF network. The GF distribution of the single-layer GF network is longitudinal and transverse (along the machine running direction), and the gram weight is about 10g / m 2 .

4. The composite film hot pressing edge sealing process according to claim 1, characterized in that: In step S7, the GF content is 0.2-0.8%.

5. The composite film hot pressing edge sealing process according to claim 1, characterized in that: In step S9, the area of ​​the heat-sealed edge is 3 to 5 cm.

6. The composite film hot pressing edge sealing process according to claim 1, characterized in that: In step S9, two shapes of patterns are used for edge banding, namely, straight edge banding and serrated edge banding.

7. The composite film hot pressing edge sealing process according to claim 1, characterized in that: In step S9, in the hot pressing edge sealing process parameters, the hot pressing temperature is 100-200°C.

8. The composite film hot pressing edge sealing process according to claim 1, characterized in that: In step S9, in the hot pressing edge sealing process parameters, the hot pressing pressure is 3 to 8 MPa.

9. The composite film hot pressing edge sealing process according to claim 1, characterized in that: In step S9, in the hot pressing edge sealing process parameters, the hot pressing time is 2 to 7 minutes.